Assessing the Experiences of Sexual and Gender Minority Applicants to Orthopaedic Surgery Residency - Douglas J. Weaver, MD; Tanios Dagher, BS; Ngoc Duong, MS; Sara Winfrey, MD; Alexander Koo, MD; Tessa Balach, MD, FAOA (JBJS Open Access)
Introduction:. The rate of sexual and gender minority (SGM) orthopaedic surgeons is far less than in other specialties, and the field has, in part, had significant difficulty attracting SGM applicants. To provide a more welcoming environment, identifying where applicants experience discrimination along medical training must be of paramount concern. Our objective was to understand the challenges faced by SGM medical students applying into orthopaedic surgery. Methods:. An anonymous survey was sent to applicants of a single orthopaedic residency program in 2023, soliciting demographics, exposure to lesbian, gay, bisexual, transgender, and/or queer (LGBTQ) mentors, and experiences with discrimination. Data were stratified by sexual orientation, and univariate analysis was conducted using chi-squared tests. Afterward, logistic regressions adjusted for gender, age, and race were performed. Results:. The overall response rate was 15.4% (n = 136/881). Fifteen percent (n = 20/135) identified as LGBTQ. Sixty-one percent of LGBTQ-identifying applicants experienced slurs and/or hurtful comments during orthopaedic rotations and research experiences, compared with 28% of their heterosexual peers (p < 0.001). In adjusted logistic regression models, LGBTQ respondents were 3.8 times more likely to report experiencing a hostile environment during training (p = 0.04) and 4.9 times more likely to have reported facing discrimination (p = 0.04) compared with heterosexual participants. Approximately 58% of respondents reported never having interacted with an LGBTQ-identifying orthopaedic attending, with only 5% reporting frequent interaction. Conclusion:. LGBTQ-identifying orthopaedic surgery applicants experience barriers related to their sexual identity, including derogatory comments, hostile clinical environments, and lack of LGBTQ mentorship. These findings highlight challenges inherent to the residency application process that may disproportionately affect persons from sexual minority groups. The recognition of such challenges can help to optimize the establishment of informed policies regarding mistreatment and practices regarding diversity and inclusion.